Allergic contact dermatitis to Aloe vera - Ferreira, M. (2011)
Abstract We present the case of a 72-year-old woman observed for dermatitis on the legs followed by apperance of erythema on the eyelids. She had a past history of peripheral venous insufficiency and had been using self home-made Aloe vera juice over the legs for relief from pain. Patch tests showed positive reactions to the leaf of Aloe, the macerated Aloe jelly, and nickel sulfate. Although most manufacturers process Aloe products avoiding its irritant extracts, and probably as a consequence reports of allergic reactions are rare, one must remember that the growing popularity on the use of Aloe products may stimulate its use ‘as is’ by the patients. Furthermore, it is important to specifically ask patients about the use of these products, because they consider it as innocuous and thus would not spontaneously provide such information